2016
DOI: 10.1097/md.0000000000003866
|View full text |Cite|
|
Sign up to set email alerts
|

Association between ideal cardiovascular health and the atherogenic index of plasma

Abstract: The American Heart Association aims to improve cardiovascular health by encouraging the general population to meet 7 cardiovascular health behaviors and factors. The atherogenic index of plasma (AIP) is an important index. Our aim is to evaluate the relationship between ideal cardiovascular health and the atherogenic index of plasma (AIP) in middle-aged Chinese men.A cross-sectional study was performed. A total of 27,824 middle-aged Chinese men were enrolled. The association between ideal cardiovascular health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 21 publications
4
58
2
2
Order By: Relevance
“…Several studies have accessed the relationship between CVH and AS markers [13,23,31]. Kulshreshtha A. et al confirmed that ideal CVH had a strong inverse correlation with carotid IMT, another preclinical marker for AS [13].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have accessed the relationship between CVH and AS markers [13,23,31]. Kulshreshtha A. et al confirmed that ideal CVH had a strong inverse correlation with carotid IMT, another preclinical marker for AS [13].…”
Section: Discussionmentioning
confidence: 99%
“…AIP was another significant predictor of AS [18,19] and was more convenient and economical compared B-mode ultrasound or CT. Shen et al indicated that the ideal CVH score correlated significantly with AIP, and a 1-point increase in the CVH score could lead to a 0.046 reduction in AIP and a 22.3% reduction in the high risk of developing AS [23]. The study subjects in the study conducted by Shen et al were middle-aged men in southeastern China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations